(untitled) (El-Wahat Journal for Research and Studies, 2025)
This Study Tackles The Pretheatrical Forms In The Algerian Heritage Because They Are A Very Important Human Heritage That Is Related To The Human Life In Its Various Aspects. The Simple Spontaneous Rituals Made Clear Images Of The Details Of The Humans’ Daily Lives And Were A Real Expression Of What They Had Lived In That Era. Besides, They Make Primary Origins Of The Theater And Have Common Features With It. Thus, We Seek Knowing Their Causes, Conditions Of Genesis, Relation And Convergence With The Theater –As A Distinct Field-, Androle In Fostering The Algerian Identity. Key Words: Forms; Play; Algerian Heritage; Origins; Identity.